Synthesis, characterization and application of a zirconium-based MOF-808 functionalized with isonicotinic acid for fast and efficient solid phase extraction of uranium(VI) from wastewater prior to its spectrophotometric determination - Marzieh Sharifi-Rad; Massoud Kaykhaii; Mostafa Khajeh; Alireza Oveisi (BMC Chemistry, 2022)
Abstract Background A zirconium-based metal-organic framework (Zr-MOF), named MOF-808, was synthesized and fully characterized by solvo-thermal method and functionalized by isonicotinic acid and employed as an efficient adsorbent for selective extraction and preconcentration of uranyl ions from water and waste water samples in a batch solid phase extraction. Results Parameters affecting extraction such as volume and pH of the sample solution, the amount of sorbent, type and volume of eluting solvent, and adsorption and desorption times were investigated and optimized. Under the optimized conditions, high extraction efficiency was observed with a limit of detection of 0.9 µg L− 1 for uranyl ions and relative standard deviations were found to be better than 2.1% in the range of 0.07–1000 µg L− 1. Conclusions These results indicated that the above procedure is fast, inexpensive, effective, reliable, applicable and organic solvent-free and showed the highly performance and stability of the Zr-MOF in SPE based analytical techniques.